The Character Values Instilled by the Main Character in the Novel Semesta Cinta Zahara by Fittriyu Siregaru - Syamsidar, Raja; Nisa'el Amala; Muhammad Alfian Tuflih; Mayong; Juli Yani (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This article aims to analyze the main characters in the novel Semesta Cinta Zahara by Fittriyu Siregaru and to identify the character values instilled by the protagonist. This qualitative descriptive research focuses on two main objectives: (1) to describe the main characters in the novel Semesta Cinta Zahara, and (2) to examine the character values embedded by the protagonist throughout the narrative. The data source for this study is the novel Semesta Cinta Zahara itself. The findings reveal that the protagonist embodies and promotes several key character values, which are grouped into three categories: (a) politeness, (b) diligence in worship and prayer, and (c) responsibility. These values are consistently portrayed through the protagonist’s actions and interactions, making the novel a potential medium for character education.